Producción de biogás y bioabonos a partir de desechos lignocelulósicos en un biorreactor de policloruro de vinilo - Cabos Sanchez, Jeisson David (2022)
Renewable energies; Biofertilizers, biofuels, etc. are an excellent alternative to non-renewable waste. are an excellent alternative to the lack of non-renewable waste, in addition to the use of waste components such as lignocellulosic waste, biofertilizers are considered excellent soil fertilizers, and the biogas produced is not toxic to the ecosystem; Therefore, the main objective of this work was to produce biogas and biofertilizers from lignocellulosic wastes in a polyvinyl chloride bioreactor, using as inoculum the rumen content of cattle as it has a high concentration of lignocellulosic bacteria; determining over time, the amount of N, P and K concentrated in the Biol and biosol, as well as the amount of biogas, produced in a biodigester. The results showed that we can obtain biogas and biofertilizers from these wastes; concluding that the maximum average concentration of biol is 242.80 ppm for Nitrogen, 1.7850 ppm for phosphorus; and, 21.8623 ppm for potassium; of biosol is 170.40 ppm for nitrogen, 1.4563 ppm for phosphorus; and, 17. 1007 ppm for potassium being 45 days the optimum biodigestion time for its maximum value, besides the biogas formation per day was 2.42 m3 from day 22; which values are related to the biodigestion time; and, under the conditions applied in the work presented.